2018
DOI: 10.3892/ol.2018.7872
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative DNA methylation analysis of paired box gene 1 and LIM homeobox transcription factor 1 α genes in cervical cancer

Abstract: Abstract. DNA methylation is associated with tumorigenesis and may act as a potential biomarker for detecting cervical cancer. The aim of the present study was to explore the methylation status of the paired box gene 1 (PAX1) and the LIM homeobox transcription factor 1 α (LMX1A) gene in a spectrum of cervical lesions in an Eastern Chinese population. This single-center study involved 121 patients who were divided into normal cervix (NC; n=28), low-grade squamous intraepithelial lesion (LSIL; n=32), high-grade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 51 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…Mersakova et al (2018) and Rong et al (2019) have recently shown that CADM1 is a potential biomarker for cervical cancer. There was a significant difference in the promoter Kan et al, 2014;Lai et al, 2014;Kong et al, 2015;Nikolaidis et al, 2015;Xu et al, 2015Xu et al, , 2018Chen et al, 2016;Liou et al, 2016;Huang et al, 2017;Fang et al, Lee et al, 2006;Yeon et al, 2018 methylation of plasma CADM1 and its D-dimer between healthy individuals and those with cervical cancer. Combining these factors to predict metastasis revealed high specificity (90.5%) and sensitivity (80.4%) (Rong et al, 2019).…”
Section: Dna Methylation In the Early Diagnosis Of Cervical Cancermentioning
confidence: 98%
See 2 more Smart Citations
“…Mersakova et al (2018) and Rong et al (2019) have recently shown that CADM1 is a potential biomarker for cervical cancer. There was a significant difference in the promoter Kan et al, 2014;Lai et al, 2014;Kong et al, 2015;Nikolaidis et al, 2015;Xu et al, 2015Xu et al, , 2018Chen et al, 2016;Liou et al, 2016;Huang et al, 2017;Fang et al, Lee et al, 2006;Yeon et al, 2018 methylation of plasma CADM1 and its D-dimer between healthy individuals and those with cervical cancer. Combining these factors to predict metastasis revealed high specificity (90.5%) and sensitivity (80.4%) (Rong et al, 2019).…”
Section: Dna Methylation In the Early Diagnosis Of Cervical Cancermentioning
confidence: 98%
“…Hypermethylated PAX1 is important in cancer progression (Huang et al, 2017) that functions in regulating cellular differentiation and proliferation (Fang et al, 2019). PAX1 can be used to detect cervical squamous cell carcinoma (CSCC) in 121 patients from eastern China with 80.9, 83.7, and 79.0% accuracy, specificity, and sensitivity, respectively (Xu et al, 2018). Combining methylated PAX1 and the presence of HPV16/18 results in an 89.2 and 76.0% sensitivity and specificity, respectively in detecting CIN3 + (Liou et al, 2016).…”
Section: Diagnostic Dna Methylation Biomarkers For Hpv-positive and Nmentioning
confidence: 99%
See 1 more Smart Citation
“…Other cellular genes, such as ADCYAP1, MAL (a T-cell differentiation protein) and CADM1 are also silenced in cells derived from UCC, due to hypermethylation of their promoters, and this condition is associated with a greater risk of tumor progression (49). Moreover, PAX1 cell genes, which encode the transcription factor paired box 1, SOX1 for the sex determining region Y-box 1 and LMX1A for LIM homeobox transcription factor 1α, all of which are involved in controlling cell division and differentiation, showed significantly higher methylation levels of their promoters in UCC cells when compared to normal cervical tissues (50,51). Finally, the RARβ gene, which is usually expressed in normal epithelial tissue, acts as a tumor suppressor when interacting with its ligand to inhibit cell migration (52).…”
Section: Epigeneticsmentioning
confidence: 99%
“…When the CpG sequence of some tumor suppressor genes CpG island is hypermethylation, it can increase the degree of chromosome helix and silencing and deletion of tumor suppressor gene, thereby inducing tumor growth [ 13 , 14 ]. Increasing evidence illustrates that DNA methylation is involved in the occurrence of tumor, and it is an important biomarker to measure various tumors [ 15 17 ].…”
Section: Introductionmentioning
confidence: 99%